ASSESSMENT OF KNOWLEDGE, PERCEPTION, ATTITUDES AND BARRIERS TO POLIO VACCINATION AMONG PARENTS - MUMTAZ , OM; YOUSAF , AI; KHAN , SU; RIZVI , Z; JAMSHAID , F; HUSSAIN , AK (Biological and Clinical Sciences Research Journal, 2024)
Polio remains a significant public health challenge in Pakistan, necessitating an understanding of parental knowledge, perceptions, attitudes, and barriers to vaccination in urban and rural areas. Objective: To assess the knowledge, perceptions, attitudes, and barriers towards polio vaccination among parents in urban and rural regions of Pakistan. Methods: A descriptive cross-sectional survey was conducted from October 2019 to February 2020, involving 609 respondents (mothers and fathers) with an 87% response rate. A pretested, anonymous, self-administered questionnaire was used to evaluate participants' knowledge, perceptions, attitudes, and barriers to polio vaccination. Results: Participants exhibited good knowledge and positive attitudes towards polio vaccination. No significant differences were noted in awareness of polio terminology between urban and rural participants (p=0.427). A majority supported polio vaccination for all children (p=0.0001*) and recognized its importance (p=0.007*). Concerns regarding vaccine sterility (p=0.0001*) were prevalent. Barriers such as lack of knowledge (p=0.216) and distrust in medical facilities (p=0.0001) were identified. Conclusion: Parents in Pakistan demonstrate good knowledge and positive attitudes towards polio vaccination. However, addressing gaps in knowledge and mistrust in medical services is critical to enhancing vaccination uptake, particularly in rural areas.